2021
DOI: 10.1111/nan.12689
|View full text |Cite
|
Sign up to set email alerts
|

Cell senescence in neuropathology: A focus on neurodegeneration and tumours

Abstract: Since the initial discovery and description of senescent cells by Hayflick and Moorhead in 1961 [1], the field of senescence has evolved and expanded immensely. Hayflick originally observed that primary human fibroblast cell cultures had a finite proliferative capacity in vitro. This finite proliferative capacity is now termed replicative senescence and is due to the gradual attrition of telomeres over serial passages [2]. It was initially proposed that replicative senescence was the driver of organismal agein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 198 publications
(290 reference statements)
0
32
0
Order By: Relevance
“…Their effects are mainly paracrine, but may become systemic as some of the soluble mediators may get into the circulation [ 257 , 258 , 259 ]. Prominent SASP regulators include p38MAPK, NFκB C/EBPβ, GATA4, and mechanistic target of rapamycin (mTOR) [ 260 , 261 , 262 ]. Senescent markers are up-regulated in the astrocytes of AD patients and Aβ elicits senescence in astrocytes in vitro via ROS accompanied by p38, IL-6, and IL-8 up-regulation [ 263 ].…”
Section: Cellular Senescence and Neuroinflammationmentioning
confidence: 99%
“…Their effects are mainly paracrine, but may become systemic as some of the soluble mediators may get into the circulation [ 257 , 258 , 259 ]. Prominent SASP regulators include p38MAPK, NFκB C/EBPβ, GATA4, and mechanistic target of rapamycin (mTOR) [ 260 , 261 , 262 ]. Senescent markers are up-regulated in the astrocytes of AD patients and Aβ elicits senescence in astrocytes in vitro via ROS accompanied by p38, IL-6, and IL-8 up-regulation [ 263 ].…”
Section: Cellular Senescence and Neuroinflammationmentioning
confidence: 99%
“…Cellular senescence is considered a potent tumor suppressive mechanism resulting in cell cycle arrest which triggers a pro-inflammatory response known as the senescence-associated secretory phenotype or SASP [ 4 , 5 ]. Since neurons are non-proliferative, they have traditionally not been considered to be capable of undergoing cellular senescence, although excessive extra- or intra-cellular stress can lead to neuronal death as well as cellular senescence [ 5 , 6 ]. Recent publications have suggested that senescence and the SASP may be strong contributing factors to PD pathology [ 4 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since neurons are non-proliferative, they have traditionally not been considered to be capable of undergoing cellular senescence, although excessive extra- or intra-cellular stress can lead to neuronal death as well as cellular senescence [ 5 , 6 ]. Recent publications have suggested that senescence and the SASP may be strong contributing factors to PD pathology [ 4 , 6 , 7 , 8 ]. However, it is still not well understood what cell-types undergo stress-mediated senescence in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations